Pendampingan Kelompok Tani Di Desa Rejosari Melalui Alih Teknologi Irigasi Menggunakan Mesin Pompa Air Sawah Berbahan Bakar Ganda - Achmad Rijanto; Suesthi Rahayuningsih; Luki Ardiantoro (CV. Multi Kreasi Media, 2023)
Partners for community service activities in the Community-Based Empowerment (PBM) scheme with the scope of Community Partnership Empowerment (PKM) were farmer groups (poktan) with the name Sari Tani Rejo Satu which was located in Rejosari village, Jatirejo sub-district, Mojokerto district, East Java province . The problems faced by partners in the field of production technology, partners still don't have rice field water pumps, so far it's from Poktan members, and the cost of fuel for water pumps was still high (gasoline or diesel), resulting in higher production costs. The aim of this PKM was to overcome the problems of partners in the field of production technology, namely the procurement of dual-fuel rice field water pumps (gasoline and gas), so that production costs are expected to decrease and ultimately have an impact on increased productivity.